Geographic heterogeneity of the epidemiological impact of the COVID-19 pandemic in Italy using a socioeconomic proxy-based classification of the national territory - Petrelli, Alessio; Ventura, Martina; Di Napoli, Anteo; Mateo-Urdiales, Alberto; Pezzotti, Patrizio; Fabiani, Massimo (Frontiers in Public Health, 2023)
Objectives This study aimed to evaluate the differences in incidence, non-intensive care unit (non-ICU) and intensive care unit (ICU) hospital admissions, and COVID-19-related mortality between the “inner areas” of Italy and its metropolitan areas. Study design Retrospective population-based study conducted from the beginning of the pandemic in Italy (20 February 2020) to 31 March 2022. Methods The municipalities of Italy were classified into metropolitan areas, peri-urban/intermediate areas and “inner areas” (peripheral/ultra-peripheral). The exposure variable was residence in an “inner area” of Italy. Incidence of diagnosis of SARS-CoV-2 infection, non-ICU and ICU hospital admissions and death within 30 days from diagnosis were the outcomes of the study. COVID-19 vaccination access was also evaluated. Crude and age-standardized rates were calculated for all the study outcomes. The association between the type of area of residence and each outcome under study was evaluated by calculating the ratios between the standardized rates. All the analyses were stratified by period of observation (original Wuhan strain, Alpha variant, Delta variant, Omicron variant). Results Incidence and non-ICUs admissions rates were lower in “inner areas.” ICU admission and mortality rates were much lower in “inner areas” in the early phases of the pandemic, but this protection progressively diminished, with a slight excess risk observed in the “inner areas” during the Omicron period. The greater vaccination coverage in metropolitan areas may explain this trend. Conclusion Prioritizing healthcare planning through the strengthening of the primary prevention policies in the peripheral areas of Italy is fundamental to guarantee health equity policies.